2008
DOI: 10.1021/ja802207p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Ionothermal Synthesis of Molecular Sieves

Abstract: AlPO4-11 and AlPO4-5 molecular sieves are ionothermally prepared without addition of water by using anhydrous starting materials, such as NH4H2PO4, pseudoboehmite (AlOOH), and NH4F. The synthesis appears to be an autocatalytic process. Water has a remarkable effect on the synthesis process. Addition of reagent quantities of water (H2O/Al = 1, molar ratio) can enhance the crystallization kinetics greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 28 publications
7
86
0
2
Order By: Relevance
“…Tian and co-workers investigated the effect of water on the ionothermal synthesis of aluminophosphate molecular sieves AlPO 4 -5 and AlPO 4 -11. [341] Their work demonstrates that water has a pronounced effect on the ionothermal synthesis of molecular sieves. Addition of reagent amounts of water can enhance the crystallization kinetics Figure 12.…”
Section: Open-framework Structuresmentioning
confidence: 99%
“…Tian and co-workers investigated the effect of water on the ionothermal synthesis of aluminophosphate molecular sieves AlPO 4 -5 and AlPO 4 -11. [341] Their work demonstrates that water has a pronounced effect on the ionothermal synthesis of molecular sieves. Addition of reagent amounts of water can enhance the crystallization kinetics Figure 12.…”
Section: Open-framework Structuresmentioning
confidence: 99%
“…It was found that the intensity of tetrahedral Al increased followed by the decrease of the octahedral Al, and the intensity of fully condensed P increased followed by the decrease of partially condensed P as the crystallization time increased. As for the 12 h sample, nearly all the Al and P atoms sit in the zeolitic framework as AlO 4 and PO 4 tetrahedrons, and are connected through the Al-O-P bonds as indicated by the 2D 27 Al, 31 P heteronuclear correlation (HETCOR) spectra.…”
Section: Resultsmentioning
confidence: 96%
“…C CP/MAS NMR spectra were recorded at 100.5 MHz with a spinning rate of 4 kHz, 2100 scans, a contact time of 2.5 ms, and a recycle delay of 2 s. 27 Al MAS NMR spectra were recorded at 104.2 MHz with a spinning rate of 10 kHz, 200 scans, and a 2 s recycle delay. The chemical shifts were referenced to a 1 % AlA C H T U N G T R E N N U N G (NO 3 ) 3 aqueous solution.…”
mentioning
confidence: 99%
“…离子热合成法采用离子液体作为溶剂和结构导向 剂, 可在常压下实现分子筛的晶化合成 [9] . 在离子热合成磷酸铝分子筛的过程中, 氟离子兼具 矿化剂和结构导向剂的作用 [16] . 而上述结果表明, 在离 子热自转晶合成 AEL 膜的过程中, 氟离子不但促进分 子筛膜晶体的成核和生长, 而且还影响了分子筛膜的生 长取向.…”
unclassified
“…P 物种是 AEL 磷酸铝分子筛骨架的组成部分之一, 磷酸铝分子筛骨架由铝氧四面体和磷氧四面体严格交 替组成, 磷铝比为 1∶1 [17] ; 成膜所需的 P 物种的量相对 较多; 而 F -在磷酸铝分子筛的晶化过程中起矿化剂和 结构导向剂的作用 [16] , 合成过程所需 F -的量相对较少. 由图 5, 6 可知, 由基底从第一步反应中携带入第二步反 应的少量 P 物种, 无法满足分子筛膜的合成所需; 而基 底从第一步反应中携带的少量 F -, 即可满足分子筛膜 的合成所需.…”
unclassified